Myositis Autoantibodies in Patients with Suspected Post-Treatment Lyme Disease Syndrome - Kristyna Sloupenska; Barbora Koubkova; Pavel Horak; Beata Hutyrova; Mojmir Racansky; Jan Mares; Martina Miklusova; Jan Schovanek; Jana Zapletalova; Milan Raska; Michal Krupka (Life, 2023)
Most patients suffering from Lyme disease are effectively treated with antibiotics. In some patients, however, problems persist for a long time despite appropriate therapy. The term post-treatment Lyme disease syndrome (PTLDS) is currently used for this condition in scientific literature. The pathogenesis is still not precisely known, but the involvement of immunopathological mechanisms is assumed. In our study, we analyzed the presence of autoantibodies including myositis-specific (MSA) and myositis-associated autoantibodies (MAA) in patients with laboratory proven history of Lyme disease and with clinical symptoms of PTLDS. A total of 59 patients meeting the criteria for PTLDS were enrolled in this study. The control group consisted of 40 patients undergoing differential diagnosis of neurological disorders without clinical and/or laboratory-proven history of Lyme disease. The presence of autoantibodies was determined by immunoblot methods and positive samples were further tested for serum creatine kinase (CK) and myoglobin levels. The presence of myositis autoantibodies was detected in 18 subjects with suspected PTLDS (30.5%), but only in 5% of control subjects exhibiting no evidence of Lyme disease history. The difference was statistically significant (p = 0.002). The subsequent biochemical analysis of muscle-damage markers in positive subjects found a mild elevation in six MSA/MAA-positive PTLDS patients. The study detected raised MSA/MAA autoantibodies formation in the group of PTLDS patients raising the question about their involvement in the pathogenesis of this syndrome.